THE EFFECT OF WORK LIFE BALANCE AND WORK ENGAGEMENT ON ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION - Sanusi, Nina Utami; arif, Nina Fapari; Arifin, Andi Harmoko (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to (1) analyze the influence of work life balance and work engagement on job satisfaction; (2) analyze the influence of work life balance, work engagement and job satisfaction on organizational commitment; (3) analyze the influence of work life balance and work engagement on organizational commitment through job satisfaction. This study was conducted at Universitas Terbuka Makassar. The sample used a purposive sampling method, namely sampling based on certain considerations or criteria. All samples amounted to 100 respondents at Universitas Terbuka Makassar. The data collection method used was direct interviews with parties involved in the problem being discussed and providing questionnaires to employees in accordance with the research being conducted. Data analysis was carried out using path analysis. The results of the analysis showed that (1) work life balance and work engagement had an effect on job satisfaction; (2) work life balance, work engagement and job satisfaction had an effect on organizational commitment; (3) work life balance and work engagement had an effect on organizational commitment through job satisfaction.